Molecular Epidemiology of Bovine Babesiosis in Punjab, Pakistan - Masih, Asif; Rafique, Azhar; Jabeen, Farhat; Naz, Shabana (Acta Scientiae Veterinariae, 2021)
Background: Babesiosis is endemic in Pakistan and is one of the most important bovine diseases that causes huge economic losses and high mortality in young animals. This disease is transmitted by a protozoan parasite babesia which belongs to genus Babesia (Apicomplexa: Piroplasmida: Babesiidae). This disease is very much prevalent in summers followed by rainy season because humid environment is favorable for the growth of these parasites. An epidemiological and molecular study was conducted to unveil the prevalence and associated risk factors of Babesia bigemina (B. bigemina) and Babesia bovis (B. bovis) in selected districts i.e., Faisalabad, Toba Tek Singh and Jhang of Punjab, Pakistan. Materials, Methods & Results: A total of 518 (Cattle = 360, Buffalo = 158) blood samples were collected. The samples were analyzed by polymerase chain reaction (PCR) and nested PCR (n-PCR) targeting apocytochrome b-genes (CYTb). Chi-square test for univariate analysis was used to analyze the data. The overall prevalence in summer based upon microscopic analysis was 20.55% (37/180) and 13.92% (11/79) in cattle and buffaloes respectively and in winter was 8.80% (16/180), 5.06% (4/79)) in cattle and buffaloes respectively. The samples were further analyzed through conventional PCR (c-PCR) and nested PCR (nPCR). The overall results of conventional PCR in summer showed that 72 cows and buffaloes were infected with babesiosis. The conventional PCR based results of summer showed that prevalence of babesiosis was 29.44% (53/180) in cows and 24.05% (19/79) buffaloes. The results of cPCR during the winter season showed that 12.77% (23/180) and 13.92% (11/79) buffaloes were positive for babesiosis. The overall results of conventional PCR in winter showed that 34/259 cows and buffaloes were infected with babesiosis. On the other hand, the nested PCR results of summer season showed that the prevalence of babesiosis in cows was 32.22% (58/180) and 29.11% (23/79) in buffaloes. In total, 81 cows and buffaloes were infected with babesiosis during summer season. The nPCR results of winter showed that 15% (27/180) cows and 20.25% (16/79) buffaloes were infected with babesiosis. In total, 43 cows and buffaloes were infected with babesiosis. The results have shown that sensitivity of n-PCR is more as compared to conventional PCR. This study is the first molecular evidence of B. bigemina and B. bovis and its associated risk factors in Punjab province, Pakistan. Discussion: Dairy sector in Pakistan is one of the fastest growing sectors. Despite of remarkable growth, dairy industry is facing many problems one of them is tick borne diseases (TBDs). TBDs are more prevalent in tropical and subtropical areas of the world and leads to huge economic losses to dairy industry in terms of decreased milk, meat and wool production. Babesiosis is characterized by increased fever, decreased production, poor quality wool, anemia, hemoglobinuria, paleness of mucous membrane. The risk factors analysis of summer and winter data revealed that, adult animals were more prone to babesiosis (24.00%) [P = 0.032] and (8.50%) [P = 0.048]. In both seasons (summer and winter), females were more infected with babesiosis (20.19% and 8.17%) [P = 0.049 and P =0.021] as compared to males, high prevalence in females was might be due to that females were reared for longer period of time. Babesiosis was more occurred in non-cemented floor system (26.01% and 13.51%) [P = 0.028 and P = 0.044] in summer and winter, respectively. Disease was found more prevalent in closed housing system in summer and winter (27.27% and 10.93%) [P = 0.043 and P = 0.034] as compared to open housing. Weak animals were more infected with babesiosis (30.84%) [P = 0.045] and (12.80%) [P = 0.042] in summer and winter, as compared to healthy ones. The animals with high tick infestations were more suffered with babesia infection (25.49% and 13.34%) [P = 0.036 and P = 0.003] in both seasons as compared to less tick burden. Keywords: apocytochrome gene, babesiosis, bovine, nPCR, PCR, season.